TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK AKAD COD PADA APLIKASI GO-FOOD DI KABUPATEN JEMBER - Abdul Ghoni (Islamic Sharia Coll, 2021)
The rise of modern transactions, there are contracts that are carried out simultaneously or cannot be left out one by one, because each of these contracts is one unit. Transactions like that are called multi contracts (hybrid contracts). One of the companies that is growing rapidly in buying and selling through online services is Go- Jek, Go-Jek has succeeded in developing its business in the field of transportation services, after that Go-Jek is growing in food delivery services called Go-food. This research is a field research (field research). Primary data was collected and conducted using the interview method between Go-Jek drivers and customers in Jember Regency. As for the secondary data, the researchers used books, works, the internet and writings related to the review of sharia economic law on the practice of COD contracts in the Go-Food application. After the research data is collected, then an analysis is carried out using a qualitative descriptive method. The purpose of this study is to find out the practice of COD contracts in the Go-food application in Jember district, to find out the COD contracts in the practice of Go-food applications in Jember district in the review of Sharia Economic Law COD contract practice via Go-Food uses 3 qardh contracts, ijarah contracts and hiwalah contracts. The collection of contracts into one is a type of multi-contract contract (al-uqud-almurakkabah). Multi-contract in practice the COD contract on the Go-Food application in Jember Regency is valid/permissible according to Sharia Economic Law.